(untitled) (Medical Forum Monthly, 2023)
Objective: To explore covid vaccination status of reproductive-age women and to determine reasons for non-vaccination among those who did not receive the vaccine. Study Design: Prospective cross-sectional multi-centre study Place and Duration of Study: This study was conducted at the department of Obstetrics & Gynaecology Dow University Hospital and Dr. Ruth K. Pfau Civil Hospital Karachi from March to May 2023. Materials and Methods: 405 women were enrolled after informed consent. Interviews with women were taped on predesigned proforma. Demographics, pregnant status, vaccination status, reasons for non-vaccination, and knowledge of vaccine indications were recorded. Results: Among 405 women,180 (44.4%) were vaccinated, and 225 (55.55%) were non-vaccinated. The mean age of vaccinated women was 30.69 years ±7.33 (CI; 29.62-31.77) versus 28.63 ± 6.5 years (CI: 27.78-29.5). In those vaccinated, nonpregnant women were in significantly higher proportion compared to pregnant; 46.66% versus 24.44 p<0.05. The most frequent reasons for non-vaccination were a concern for active disease 19.11% and adverse effects on fertility 18.66%, followed by the influence of family 15.55%, concerns for transmission to fetus in Pregnancy (10.66%) and thinking the vaccine was unnecessary (9.77%) Conclusion: Significant proportion of our reproductive-age women is non-vaccinated due to their concerns about getting diseases following vaccination, adverse effects on fertility, transmission to the fetus during Pregnancy and influence by family.